Differential modulation of BMP signaling promotes the elaboration of cerebral cortical GABAergic neurons or oligodendrocytes from a common sonic hedgehog-responsive ventral forebrain progenitor species - Yung, Shau-Yu (National Academy of Sciences, 2002)
During cerebral cortical development, excitatory glutamatergic projection neurons are generated from neural stem cells intrinsic to the early embryonic cortical ventricular zone by a process of radial migration, whereas most inhibitory γ-aminobutyric acid (GABA)ergic interneurons and oligodendrocytes (OLs) appear to be elaborated from ventral forebrain stem cells that initially undergo tangential cortical migration before terminal lineage maturation. In contrast to the more compartmentalized developmental organization of the spinal cord, the generation of neurons and OLs from a common ventral forebrain stem cell would expose these cells to the sequential actions of ventral and dorsal gradient morphogens [sonic hedgehog (Shh) and bone morphogenetic proteins (BMPs)] that normally mediate opposing developmental programs. Here we report that Shh promotes GABAergic neuronal/OL lineage restriction of forebrain stem cells, in part, by activation of the basic helix–loop–helix transcription factors, Olig2 and Mash1. In mutant mice with a generalized defect in tangential cortical migration (Dlx1/2−/−), there is a profound and selective reduction in the elaboration of both cortical GABAergic neurons and OLs. Our studies further demonstrate that the sequential elaboration of cortical GABAergic neurons and OLs from common Shh-responsive ventral forebrain progenitors requires the spatial and temporal modulation of cortical BMP signaling by BMP ligands and the BMP antagonist, noggin, respectively. These findings suggest an integrative model for cerebral cortical GABAergic neuronal and OL lineage maturation that would incorporate the sequential contributions of the ventral and dorsal forebrain, and the potential role of regional developmental cues in modulating transcriptional codes within evolving neural lineage species.